Eksplorasi Etnomatematika Pada Batik Samer Jumputan Di Sentra Batik Ayu Kedunggudel Sukoharjo - Nazahra, Sevia; Astutiningtyas, Erika Laras (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
Abstract This study aims to explore the concept of ethnomathematics in Samer Jumputan batik at Sentra Batik Ayu, Kedunggudel, Sukoharjo. This motif combines Javanese and Kalimantan cultural elements, such as wajik, jumputan, samer, bulu ruai, and wallet. The research employs a qualitative method with an ethnographic approach, including observation, interviews, and documentation to obtain comprehensive data. The study reveals the concepts of geometric transformation, including translation, reflection, rotation, dilation, and transformation combinations in batik patterns. The findings indicate that the Samer Jumputan motif can be used as a contextual medium in mathematics learning, particularly in geometric transformation concepts. In addition to enhancing students' understanding of mathematical concepts, this study also strengthens appreciation for local culture. Thus, batik serves as an effective educational tool while enriching culture-based learning.  Keywords: Batik Samer Jumputan, ethnomathematics, geometric transformation, culture-based learning